Biogas untuk Menghasilkan Energi Listrik - Paniran; rosmaliati; Abdul Natsir (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2023)
Biogas is a methane gas produced from the fermentation of organic matter by anaerobic bacteria. Utilization of biogas as an energy source can be done by burning biogas directly, and indirectly by converting it into electrical energy. Biogas-fueled electric energy potential to be developed in the NTB area. The fundamental reason is: the government program